One-Year Outcomes of 1 Dose versus 3 Loading Doses Followed by Pro Re Nata Regimen Using Ranibizumab for Neovascular Age-Related Macular Degeneration: The ARTIS Trial. (10th October 2019) - Wang, Fenghua; Yuan, Yuanzhi; Wang, Ling; Ye, Xiaofeng; Zhao, Jingke; Shen, Mengxi; Zhang, Qi; Xu, Ding; Qin, Guoyou; Zhang, Wei; Yuan, Fei; Chang, Qing; et al.
Abstract : P urpose . To compare the functional and anatomical outcomes of one dose and three loading doses followed by the pro re nata (PRN) regimen in Chinese neovascular age-related macular degeneration (nvAMD) (including polypoidal choroidal vasculopathy (PCV)) patients. Methods . In this multicenter, prospective, open-label, controlled, 12-month study (ClinicalTrials.gov:NCT02810808 ), patients were randomized (1 : 1) to 1 dose + PRN (PRN group) or 3 loading doses + PRN (LD group) using intravitreal ranibizumab treatment. Best-corrected visual acuity (BCVA) and central retinal thickness (CRT) were evaluated. The main outcome was the change in BCVA. The noninferiority limit was 5 letters. Results . Forty-five patients in the PRN group and 49 patients in the LD group finished 12-month follow-up. Each group included 4 PCV patients. The mean change in BCVA from baseline was 7.8 letters in the PRN group, compared with 10.9 letters in the LD group (P = 0.344 ). There were no significant differences between two groups in the mean change of CRT (−159.3 μ m vs. −120.5 μ m) at month 12. The mean number of injections during the 12-month follow-up was 6.0 in the PRN group and 6.8 in the LD group. The proportion of patients who gained an improvement in visual acuity by 15 or more letters was 28.9% in the PRN group and 44.9% in the LD group (P = 0.066 ). Conclusion . One dose + PRN showed noninferior visual gains than 3 loading doses + PRN regimen using ranibizumab in Chinese nvAMD and PCV patients. Number of injections in the PRN group was similar as that in the LD group but remained a potential risk of vision instability during one-year follow-up using OCT-guided retreatment criteria. This trial is registered withNCT02810808 .